Clinical methods in ophthalmology a practical manual for medical students - K. Dadapeer (Jaypee Brothers Medical Publishers (P) Ltd, 2015)
In the second edition of the book, all chapters have been edited and re-written including new definitions, new concepts, and new photographs have been added. A new chapter on Community Ophthalmology has been added